Evaluasi Persediaan dan Hubungannya dengan Produktivitas - Fitri Ramadhani; Ismail Badollahi; Wa Ode Rayyani (Jurnal Ekonomi Islam, 2026)
This study analyzes the planning, implementation, and evaluation of inventory management and its relationship with productivity at PT Sinergi Gula Nusantara, Camming Sugar Factory, Bone Regency. Using a descriptive qualitative method, the researchers collected data through interviews, observation, and documentation from key informants (Acting Factory Manager, Warehouse Head, and Production Admin) and analyzed them using the Miles and Huberman model. The results indicate that inventory management is not yet optimal: the planning stage still relies on experience-based estimates that often miss the mark; the implementation stage applies the Just-In-Time concept but still faces accumulation issues due to machine capacity limitations; and the evaluation stage remains simple, without structured indicators. This condition has been proven to disrupt smooth production, trigger stock imbalances, and suppress company productivity. The company is advised to improve its planning, control, and evaluation systems in a structured manner to enhance operational efficiency.